The Impact of the Establishment of Youth Integrated Health Posts on Increasing CERDIK Knowledge in Sungai Duren Village - Adila Solida; Andy Amir; Evy Wisudariani (International Journal of Public Health, 2025)
The incidence of degenerative diseases, which are part of Non-Communicable Diseases (NCDs), remains a major cause of death worldwide and in many regions of Indonesia. Meanwhile, efforts to prevent degenerative diseases affecting the adolescent age group are still rare, such as the establishment of a Youth Posyandu, including in Sungai Duren Village. There is no health post that provides youth care services in Sungai Duren Village, while there are many teenagers living there (students under 21 years old) with various lifestyles that are at risk of degenerative diseases. This study aims to analyze the increase in adolescent knowledge about CERDIK between before and after the establishment of the Youth Posyandu in order to prevent degenerative diseases early. This study is a quasi-experimental study involving 30 adolescents by measuring the dependent variable of knowledge. The research instrument used is a questionnaire. Computerized data processing and analysis were conducted through descriptive statistical analysis and T-test analysis. The results showed a significant difference in respondents' knowledge of CERDIK before and after the establishment of the Youth Posyandu in Sungai Duren Village (p=0.000). This study indicates that structured health education can improve adolescents' understanding of CERDIK and can be used as an effective promotive and preventive strategy.